Ultrasonically synthesized TiO2/ZnS nanocomposites to improve the efficiency of dye sensitized solar cells. (September 2021) - Sekar, Ramkumar; Sivasamy, Ramesh; Ricardo, Báez; Manidurai, Paulraj
Abstract: TiO2 /ZnS nanocomposites were synthesized using facile ultra-sonication method. Structural, morphological and optical properties of as-synthesized nanocomposites were investigated. The X-Ray diffraction pattern exhibits anatase phase of TiO2 without the influence of ZnS phases in the composites. Morphology of the samples were studied using TEM which confirmed the presence of discrete globular like particles. Optical absorption spectra of the nanocomposites showed an enhancement in UV–Vis region. DSSC were fabricated using the synthesized nanocomposites as a secondary layer grown over FTO/TiO2 photoanode. Amongst the constructed cells TiO2 with 1% ZnS showed the highest efficiency of about 4.1% which is an enhancement of 27.7%, higher than that obtained for pure TiO2 . Graphical abstract: Image 1 Highlights: Facile ultra-sonication method was adopted to prepare ZnS/TiO2 nanocomposites. XRD, Raman and UV–Vis absorption spectra was analysed in detail. DSSC devices fabricated using nanocomposite as secondary layer. 27% efficiency enhancement achieved when 1 wt% ZnS dopant was incorporate with TiO2.